2021
DOI: 10.1073/pnas.2101287118
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro vesicle formation assay reveals cargo clients and factors that mediate vesicular trafficking

Abstract: The fidelity of protein transport in the secretory pathway relies on the accurate sorting of proteins to their correct destinations. To deepen our understanding of the underlying molecular mechanisms, it is important to develop a robust approach to systematically reveal cargo proteins that depend on specific sorting machinery to be enriched into transport vesicles. Here, we used an in vitro assay that reconstitutes packaging of human cargo proteins into vesicles to quantify cargo capture. Quantitative mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 54 publications
10
25
0
Order By: Relevance
“…Deletion of SURF4 resulted in significantly reduced secretion of 10 proteins in HEK-293 cells and 18 in HuH7 cells (Figure 4C, D, Table S1). Consistent with previous observations, NUCB1 and NUCB2 were among the top hits affected in SURF4KO cells (Huang et al , 2021). Nucleobindins, together with Cab45, overlap as SURF4-dependent hits between the two cell lineages (Figure 4E).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Deletion of SURF4 resulted in significantly reduced secretion of 10 proteins in HEK-293 cells and 18 in HuH7 cells (Figure 4C, D, Table S1). Consistent with previous observations, NUCB1 and NUCB2 were among the top hits affected in SURF4KO cells (Huang et al , 2021). Nucleobindins, together with Cab45, overlap as SURF4-dependent hits between the two cell lineages (Figure 4E).…”
Section: Resultssupporting
confidence: 92%
“…Since multiple diverse cargo proteins interact with the Sec24 B-site (Miller et al , 2003; Mossessova et al , 2003; Mancias & Goldberg, 2008; Ma et al , 2017), perturbing SURF4-client interaction may represent a more tractable way forward to therapeutic intervention. However, the client repertoire of SURF4 seems substantial (Yin et al , 2018; Ordonez et al , 2021; Huang et al , 2021), and being able to selectively inhibit a subset of receptor-cargo interactions may be difficult. Nonetheless, like SEC24, SURF4 also appears to be a multivalent export facilitator, since it also recognises a second ER export signal, the Cardin-Weintraub (CW) motif, found on Shh (Tang et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the transporter activity was the most abundant category in the molecular function (Figure 4B). Vesicles play a key role in protein transport [29], and the difference in protein transport activity may be related to milk protein components in HL yak milk. The KEGG pathway enrichment analysis, which was based on the DEPs, revealed that the metabolic pathways with the most differences were those that involved carbohydrate metabolism, the biosynthesis of amino acids, and fat digestion and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The vesicle formation assay is another way to identify the Arf regulators or Arf effectors (Huang et al, 2021). During this approach, the vesicle formation assay was performed in the presence or absence of the GTP-locked form of a specific ARF family protein.…”
Section: Experimental Approaches To Study the Functional Roles Of Arf...mentioning
confidence: 99%
“…This approach has an advantage to identify the Arf binding partners in conditions that lipid bilayer is not disrupted. Using this approach, a novel cytosolic factor, PRRC1, was identified to interact with Sar1A in a GTPdependent manner on vesicle membranes (Huang et al, 2021).…”
Section: Experimental Approaches To Study the Functional Roles Of Arf...mentioning
confidence: 99%